Protocol for identifying key genes using network-based approach as an alternative to differential expression analysis - Piyush Agrawal; Sridhar Hannenhalli (STAR Protocols)
Summary: In a variety of biological contexts, characterizing genes associated with disease etiology and mediating global transcriptomic change is a key initial step. Here, we present a protocol to identify such key genes using our tool “PathExt,” a tool that implements a network-based approach. We describe steps for installing libraries, preparing input data and detailed procedures for running PathExt, and characterizing differential pathways and key genes based on ripple centrality scores.For complete details on the use and execution of this protocol, please refer to Agrawal et al.1,2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.